A Validation Study of the Human Perception of Virtual Characters’ Features - Freitas, Georgy L. J. de; Silva, André Gustavo Pereira da; Paradeda, Raul Benites (Anais do Encontro de Computação do Oeste Potiguar ECOP/UFERSA (ISSN 2526-7574), 2023)
Several digital games use virtual characters to provide further immersion and interactivity to the player. In specific tasks, these characters can be used to influence players’ decision-making. However, the player’s perception of a virtual character is not always the one that was designed for that character. For example, when a character that was designed to cause fear in the player but does not. In this sense, this paper describes a quantitative study validation of the appearance of virtual characters that will be used in an interactive narrative game. The participants informed their perceptions regarding the nature, clothes, and behavior of 40 characters designed for this study. From the results, it can be inferred that player characteristics, such as gender and age, can influence the character’s perception. Another result observed was that differences in visual aspects (e.g., well or poorly dressed) are better perceived when compared to differences between behavioral characteristics (e.g., honest and dishonest).